The Making of Muslim Millennial Moderate Identities through Sufistic Multicultural Da'wah (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
Multicultural - Sufistic Da'wah is interesting to discuss, considering that multicultural and Sufistic preaching has long been a feature of Islamic preaching in Indonesia. However, in its development, the pattern of people's lives has undergone significant changes. One of them is the rapid growth of information and communication technology that has created a spiritually fragile millennial. The role of multicultural and Sufistic preaching is considered very important in guarding millennial Moslem's life. This article concludes that Sufistic da'wah's need is significant for the millennial generation to guide spirituality and modern religious identity through a qualitative approach with this type of literature study research. At the same time, growing diversity requires a complementary approach, namely the preaching of multiculturalism to guard the plurality of diversity in the millennial era. The two of them have a significant relationship to reach the Ulul Albab generation